Technical Approaches to Developing a Highway Noise Programmatic Agreement. Issue 1 (January 2019) - Alexander, Adam; El-Aassar, Ahmed; MacDonald, John; Martin, Anjoli
There are many instances in which noise studies were completed for projects that were not likely to result in noise impacts. In this paper, the authors provide an analysis from their conducted study, validating a programmatic agreement (PA) intended to reduce the need for unnecessary noise analyses. The technical study considered a range of average daily traffic volumes between 500 and 28, 000. The parameters of the PA rely solely on calculated noise levels at specified traffic volume, mix, speed, and roadway designs using the FHWA Traffic Noise Model (TNM®) version 2.5 to develop a series of TNM cases, testing impact thresholds at various speed and slope conditions. Using this data, the authors developed a regression model to enable the PA expansion and provide answers for a finer grid of traffic volume. Using the regression model results, the authors will develop a graphical user interface to assess project eligibility for the PA.